Increasing G9a automethylation sensitizes B acute lymphoblastic leukemia cells to glucocorticoid-induced death - Poulard, Coralie (Cell Death Dis, 2018)
Synthetic glucocorticoids (GCs) are used to treat lymphoid cancers, but many patients develop resistance to treatment, especially to GC. By identifying genes that influence sensitivity to GC-induced cell death, we found that histone methyltransferases G9a and G9a-like protein (GLP), two glucocorticoid receptor (GR) coactivators, are required for GC-induced cell death in acute lymphoblastic leukemia (B-ALL) cell line Nalm6. We previously established in a few selected genes that automethylated G9a and GLP recruit heterochromatin protein 1γ (HP1γ) as another required coactivator. Here, we used a genome-wide analysis to show that HP1γ is selectively required for GC-regulated expression of the great majority of GR target genes that require G9a and GLP. To further address the importance of G9a and GLP methylation in this process and in cell physiology, we found that JIB-04, a selective JmjC family lysine demethylase inhibitor, increased G9a methylation and thereby increased G9a binding to HP1γ. This led to increased expression of GR target genes regulated by G9a, GLP and HP1γ and enhanced Nalm6 cell death. Finally, the KDM4 lysine demethylase subfamily demethylates G9a in vitro, in contrast to other KDM enzymes tested. Thus, inhibiting G9a/GLP demethylation potentially represents a novel method to restore sensitivity of treatment-resistant B-ALL tumors to GC-induced cell death.